My green city : back to nature with attitude and style - Klanten, Robert; Ehmann, Sven.; Bolhöfer, Kitty (Berlin : Gestalten, 2011)
"The last few decades were dominated by the urban, the digital, and the sleek as well as a notable esteem for speed and consumption. Today, a growing countermovement is advocating for a sustainable and more responsible way of dealing with our environment and bringing nature back to our cities. My Green City celebrates this turnaround as well as the way of life and creativity of the designers, artists, architects, activists, and passionate laypeople involved. The book presents inspirational projects from around the world - from urban farming initiatives and architectural visions that are changing our cities as a whole, to furniture and other everyday objects that can make our own streets and homes greener. Guerilla gardeners are decorating urban eyesores with flowers. Glamping resorts offer hip, yet environmentally friendly vacations amid beautiful landscapes. Designers are creating projects, products, and works of art that use plants in a functional or aesthetic way - or are perhaps just trying to get people to think differently. My Green City is an entertaining and socially relevant compilation for everyone who has an interest in a more responsible and environmentally friendly lifestyle. The book shows us how we can care for our planet without falling into hopelessness or dwelling on a bad conscience. Its manifold visual examples and insightful descriptions make it clear that we can instead design our urban future in a way that is green, innovative, vibrant, and constructive. "--Publisher's description.
Includes index.
boek